A Study on the Relationship Between Emotion Regulation and Grit Among College Foreign Language Teachers - Jia, Sheng; Dong, Hui (Journal of Educational Research and Policies, 2025)
Research on teacher emotion regulation and teacher grit has recently emerged as a new focus in the field of foreign language education. At present, the relationship between the two still leaves much room for further exploration. This study centers on college foreign language teachers in China, adopting a mixed-methods approach. It uses SPSS 27.0 for statistical analysis of questionnaire data and NVivo 12 for coding and thematic analysis of interview materials to empirically investigate the correlation between teacher emotion regulation and teacher grit. The results indicate that the overall levels of emotion regulation and grit among college foreign language teachers are at an upper-medium level, with the scores of most subdimensions (except for “situation selection”) being above the medium level, albeit with some variations. A moderate positive correlation was found between the two variables. Among the teacher emotion regulation strategies, “suppression” showed the highest correlation with teacher grit. Based on these findings, this paper suggests that greater attention should be given to teachers’ emotions and that a positive ecological environment should be fostered to support the development of both teacher emotion regulation and teacher grit.